Roofing Materials Assessment: Investigation of Five Metals in Runoff from Roofing Materials. (1st September 2015) - Winters, Nancy; Granuke, Kyle; McCall, Melissa
ABSTRACT: : To assess the contribution of five toxic metals from new roofing materials to stormwater, runoff was collected from 14 types of roofing materials and controls during 20 rain events and analyzed for metals. Many of the new roofing materials evaluated did not show elevated metals concentrations in the runoff. Runoff from several other roofing materials was significantly higher than the controls for arsenic, copper, and zinc. Notably, treated wood shakes released arsenic and copper, copper roofing released copper, PVC roofing released arsenic, and Zincalume® and EPDM roofing released zinc. For the runoff from some of the roofing materials, metals concentrations decreased significantly over an approximately one‐year period of aging. Metals concentrations in runoff were demonstrated to depend on a number of factors, such as roofing materials, age of the materials, and climatic conditions. Thus, application of runoff concentrations from roofing materials to estimate basin‐wide releases should be undertaken cautiously.